Effects of nicotine on cytochrome P450 2A6 and 2E1 activities - Hukkanen, Janne (Blackwell Science Inc, 2010)
AIMS: Smoking slows the metabolism of nicotine and accelerates the metabolism of chlorzoxazone, which are probe reactions for cytochrome P450 2A6 (CYP2A6) and CYP2E1 activities, respectively. We aimed to determine the role of nicotine in these metabolic effects of cigarette smoking. METHODS: The study had a single-blind, randomized, crossover two-arm design. Twelve healthy smokers were given two transdermal patches with 42-mg nicotine a day or placebo patches, each for 10 days. The subjects abstained from smoking during the study arms. Oral chlorzoxazone was given on day 7 and deuterium-labelled nicotine-d(2) and cotinine-d(4) infusion on day 8. RESULTS: There was no significant influence of transdermal nicotine administration on pharmacokinetic parameters of nicotine-d(2) or on the formation of cotinine-d(2). Nicotine decreased the volume of distribution (62.6 vs. 67.7 l, 95% confidence interval of the difference −9.7, −0.6, P= 0.047) of infused cotinine-d(4). There were no significant differences in disposition kinetics of chlorzoxazone between the treatments. CONCLUSIONS: CYP2A6 and CYP2E1 activities are not affected by nicotine. The tobacco smoke constituents responsible for the reduced CYP2A6 and increased CYP2E1 activities remain unknown.